BENCHMARKING OF INSURANCE PRODUCTS IN LATVIAN INSURANCE INDUSTRY - Janovs, Valdis; Fomin, Vladislav V. (European Scientific Journal, ESJ, 2013)
To date there are no guidelines, laws, or standards in Europe to define how to market to consumers products, which are complex, information-rich, and hence cannot be easily compared to facilitate consumer purchase decision. Direct price/quality comparison of available insurance services is virtually impossible due to complex informational nature of the product and the role of intermediaries, who often market the products based on insurer’s reputation and its “closeness” to that particular intermediary. As a result, consumers receive impartial information on the comparable standing of competing products, which results in sub-optimal functioning of the market. The purpose of this paper is to examine the product marketing information channels and methods in Latvian non-life insurance segment, and to identify whether consumers can receive comparable information on competing insurance products. This work is based on a case study. Data is collected using interviews with insurance brokers, and desk research.